PENGARUH PROFITABILITAS, LEVERAGE, INVESTMENT OPPORTUNITY SET, DAN LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL MODERATING (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Ghina Ahsanatul; Yusralaini Yusralaini; Hariyani Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
The purpose of the study is to find out about (1) Effect of profitability ondividend policy, (2) Effect of leverage on dividend policy, (3) Effect of investmentopportunity set on dividend policy, (4) Effect of liquidity on dividend policy, (5) Moderatecompany value the influence of profitability on dividend policy, (6) Company valuemoderates the influence of leverage on dividend policy, (7) Firm value moderates theinfluence of investment opportunity set on dividend policy, (8) Firm value moderates theeffect of liquidity on dividend policy. The sampling method used in this study was thepurposive sampling method for the period 2015-2017 in the Indonesian stock exchange at154 manufacturing companies and 23 observational samples with moderation regressionas an analysis technique. The statistical test tool used is the Statistical Product andServices Solution (SPSS) program version 17.0, while the data used is in the form of NetIncome After Taxes per Total Asset (ROI), Total Liabilities per Total Shareholder Equity(DER), Total Fixed Assets per Total Asset (CAPBVA), Current Total Assets per CurrentLiability (CR), Dividend Per Share per Earning Per Share (DPR), and Share Price PerShare Share per Book Value Per 1 Sheet of Stock (PBV) for the period 2015-2017. Theresults showed that profitability had no effect on dividend policy, leverage affecteddividend policy, investment opportunity set had no effect on dividend policy, liquidity hadan effect on dividend policy. Furthermore, through the tests carried out in this study theresults showed that the company value was not able to moderate the effect of profitabilityon dividend policy, the value of the company was able to moderate the influence ofleverage on dividend policy, firm value was not able to moderate the effect of investmentopportunity set on dividend policy, and firm value moderate the effect of liquidity ondividend policy.Keywords : Dividend Policy, Company’s Value, Profitability, Leverage, InvestmentOpportunity Set (IOS), Liquidity